Anti-Hyperuricemic Effects of Oenanthe javanica Extracts in Hyperuricemia-Induced Rats - Woo-Ju Lee; Ho-Sueb Song (MEDrang Inc., 2023)
Background: This study aimed to investigate the effects of Oenanthe javanica (OJ) extracts on rats with potassium oxonate (PO)-induced hyperuricemia. Methods: The effects of OJ extract on rats with PO-induced hyperuricemia-induced were monitored. Changes in the body weight and organ indices of hyperuricemic rats were calculated to detect anti-hyperuricemic effects. Blood samples were collected to observe the effect of reducing serum uric acid concentration. Kidney tissues were stained to observe histopathological changes under a microscope. The activity of xanthine oxidase (XO), which catalyzes xanthine to uric acid in the liver, was assessed to observe the inhibitory effect of XO. Results: 1. The body weight of hyperuricemic rats showed no considerable differences between the control group and the treatment group. The OJ group had significantly improved liver index, whereas the allopurinol group had improved liver and kidney indices. 2. Serum uric acid levels increased significantly after PO injection, and the OJ and allopurinol groups showed a significant reduction effect. 3. PO injection led to the inflammation of kidney tissues, and OJ improved it significantly. 4. The activity of XO after PO injection was significantly increased, and allopurinol significantly inhibited XO activity in the liver. Conclusion: In the hyperuricemia rat model, OJ extract reduced uric acid concentration and demonstrated its anti-inflammatory effects. Thus, OJ extracts can be used to lower uric acid levels.